Raised CA125 – what we actually know…. (2nd December 2020) - Howe, Tamara; Sokolovsky, Nava; Sayasneh, Ahmad; Omar, Kazal; Tahmasebi, Farshad
Abstract : Key content: Carbohydrate antigen 125 (CA125) is an antigen used in the diagnosis of epithelial nonmucinous ovarian cancers. CA125 may be elevated in many benign and malignant conditions, so elevated levels can cause confusion over patient management. The multidisciplinary team is important when planning care for patients with suspected ovarian cancer. Learning objectives: To know the factors leading to CA125 production and its mechanism of action. To understand how CA125 is used as a diagnostic tool and to assess the treatment response of ovarian cancer. To appreciate patient care options in cases of falsely elevated CA125. Ethical issues: Is the CA125 blood test being used in patients appropriately and safely? In patients with elevated CA125 levels, does this lead to unnecessary investigations and invasive treatments?